Application of business intelligence to improve decision-making in the marketing of hardware companies in Peru - Ogosi Auqui, José Antonio (2023)
21st LACCEI International Multi-Conference for Engineering, Education, and Technology & 4th CLADI-CONFEDI: “Leadership in Education and Innovation in Engineering in the Framework of Global Transformations: Integration and Alliances for Integral Development”, Hybrid Event, Buenos Aires - Argentina.